Factors effecting online shopping behaviour with trust as moderation - Bhatti, Anam; Ur Rehman, Shafique; Kamal, Ahtisham Zahid; Akram, Hamza (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of this research is to study financial risk, product risk, privacy risk, and convenience risk influence on internet buying behaviour with trust as moderator. For this purpose, data were gathered from students that are studying in HEC recognized universities in Punjab, Pakistan. Five hundred fifty questionnaires were used for analysis by using the partial least square equation modeling technique. Outcomes reveal that financial risk, product risk, and privacy risk significantly decrease online shopping behavior. Trust significantly enhances online shopping behaviour. Trust moderates between (product risk, privacy risk, and convenience risk) and online shopping behaviour. This research is the pioneering research that tests the moderating role of trust between financial risk, product risk, privacy risk, convenience risk, and internet buying behaviour by using TPB theory and SET theory.